TRILATERALISM AND ISSUES OF COOPERATION BETWEEN THE UNITED STATES, JAPAN AND WESTERN EUROPE - A. I. Pechalova (Vestnik MGIMO-Universiteta)
The article deals the phenomenon of trilateralism – the term used to describe relations between theUnited States of America,JapanandWestern Europe. The article presents an overview of factors that encourage closer ties between the regions as well as an analysis of trends that may potentially cause the collapse of the trilateral format.The factors that have initially created trilateralism include common political approaches, a shared economic demand and a strong need for energy security. Though these components remain an important part of trilateral relations; the range of factors that affect trilateralism is much wider today than four decades ago.Risks that may lead to the disruption of trilateralism are identified. Firstly, trilateral relations are strikingly asymmetrical: ties between theUS,JapanandWestern Europedevelopat different ratesand an evident disproportion exists in sharing responsibilities. Namely, bilateral relations between theUSandJapanand theUSand Western Europe are closer than the cooperation betweenJapanandWestern Europe.Secondly, there is a divergence in foreign policy priorities of the countries. With European priorities lying within the European Union, further integration and relations with the neighbors andJapanactively monitoring the developments in the Asia-Pacific, theUShas yet to articulate its foreign policy.Thirdly, economic issues that used to bethe core of relations between the three sides during the Cold Warare gradually disappearing from the trilateral agenda. An analysis oftask force reports to Trilateral Commission – an expert format that embodies trilateral relations – demonstrates the tendencies mentioned above.The author comes to the conclusion that trilateralism is on the verge of change. Its future mainly depends on the choice of issues for further cooperation and on the effectiveness of the format in dealing with global problems as they arise.